1996
DOI: 10.1097/00042560-199611010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal HIV Infection with Low Birth Weight

Abstract: We evaluated factors associated with low birth weight (LBW) in an HIV-infected cohort (n = 772) and a general sample (n = 2,377) of women delivering a live singleton in federal fiscal years 1989 and 1990 while enrolled in New York State Medicaid. The association of LBW and HIV infection was studied in logistic models, controlling for illicit drug use, demographic characteristics, adequacy of prenatal care, and medical risk factors. Overall, 29% of the HIV-infected women had a LBW infant compared to 9.3% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 28 publications
2
22
0
3
Order By: Relevance
“…Due to the low rates of the other pregnancy and labor and delivery complications, an indicator variable was created for those complications associated with an increased risk of low birth weight. 25 This variable indicated the presence of at least one of the following pregnancy complications: cardiac disease, chronic hypertension, eclampsia, lung disease, preeclampsia, renal disease, and uterine bleeding. An indicator variable also was created for labor and delivery complications: abnormal presentation, abruptio placenta, amnionitis and sepsis, cord prolapse, fever, labor eclampsia, placenta previa, precipitous labor, and labor preeclampsia.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the low rates of the other pregnancy and labor and delivery complications, an indicator variable was created for those complications associated with an increased risk of low birth weight. 25 This variable indicated the presence of at least one of the following pregnancy complications: cardiac disease, chronic hypertension, eclampsia, lung disease, preeclampsia, renal disease, and uterine bleeding. An indicator variable also was created for labor and delivery complications: abnormal presentation, abruptio placenta, amnionitis and sepsis, cord prolapse, fever, labor eclampsia, placenta previa, precipitous labor, and labor preeclampsia.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, HIV-positive women are more likely to terminate their pregnancies, give birth to low birth weight babies, deliver preterm or experience stillbirths [106][107][108][109]. For the purpose of this review, both therapeutic and preventive preconception measures to reduce HIV infection were examined.…”
Section: Hiv/aids Prevention Strategiesmentioning
confidence: 99%
“…1 HIV-infected women on Medicaid are a key target for such an initiative because they are twice as likely to bear a low-birthweight child as uninfected women on Medicaid. 23 New York's efforts appear to be richly rewarded; we found that program care was associated with at least a 40% reduction in the adjusted odds of preterm delivery in our study population of 1700 HIV-infected women.…”
Section: Discussionmentioning
confidence: 61%